Improving Student Learning Activities through the Problem Based Learning Model in Islamic Learning at SD Negeri Rantau Gedang - Mawarni, Samsi; Jambeh, Abdul (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research is entitled